The Pure and Powerful - Heba Raouf Ezzat (International Institute of Islamic Thought, 1999)
While most of the literature on Islam over the past two decades has concentrated on the issue of Islamic resurgence, focusing mainly on the nature and workings of political movements and militant Islamic groups, this book examines instead the beliefs and practices of ordinary Muslim, exploring an intricate web of social relationships involving the 'ulama, government, Islamic institutions, Sufis, and the people Jiving in the rural and city areas of the country. The analysis demonstrates how in order to further our understanding of Muslim society, we must gather fieldwork data on the relationship of the common person's Islamic practices to those of the Islamic tradition and apply the relevant analytical concepts to examine them. It further challenges the existing ethnography of Muslim society which is not only based mainly on limited empirical data but also conceals issues worthy of study and is, moreover, full of assumptions oversimplifying the nature of the complex social relationships involved. For instance, anthropology implicitly assumes that the "native" is a naive and ignorant person who, as a corollary of this, is ignorant of his own religion. The consequence of this supposition has been that anthropologists who have written on the subject have not found it necessary to examine how the Islamic practices of the common people have been related to the Islamic tradition. It was also often assumed that the Islamic knowledge of the 'ulama, and their status as the learned ones, somehow separated them from the lives of the common people. Only recently have researchers started studying the effect of their fa tawa on society and people, little work having been done before on their lives and influence. This work refutes the assumption that the Islamic text is outside society and that the 'ulama are an entity separate from the people. The author re-examines the view that different societies contain different versions of Islam and points out that this type of thinking does not of itself advance our knowledge of the subject, nor does it offer a viable criteria for ...